Keanekaragamaan dan Pemanfaatan Tumbuhan Obat Tradisional Pada Masyarakat di Kelurahan Lipu Kecamatan Betoambari Kota Baubau Provinsi Sulawesi Tenggara - Indrawati Indrawati; Yusuf Sabilu; Puji Fitria Zainal (University of Halu Oleo, 2015)
The use of plants as traditional medicine has been known since long time ago by people in Lipu. This process has been inherited from one to next generation, nevertheless. nowdays, it has started to be extincted. So, it should be better to indentify the species of plant used as traditional medicine by people in Lipu. The research aims to investigate thekinds of plant which uses as traditional medicine. The part of plant used and how to process and the adventage of the plant. The research used explorative survey method. The result of the research there are 54 species from 31 family of plants used as traditional medicine by the people. The parts used of plant are leaf, stem/bark, root, flower, fruit, seed, tuber,rhizome and sap. The processing of the plants by refine, boil, squeeze, parch, pour boiling water, rasp and without processing. And the ability of the plants are can treat kinds of disease.